Pengaruh Temperatur Rendah pada Sifat Bending dari Pipa Komposit Epoxy dengan Penguatan Serat Jute - I.A.N Pramadyanti; I.K Adi Atmika; I.D.G Ary Subagia (INDONESIAN JOURNAL OF APPLIED PHYSICS, 2021)
The experiment about the bending behavior of pipe composite based under the low-temperature treatment was carried out. As for the background of this research is that composite material become a suitable design with user need and it has behavior to substitute metal in engineering products. The research aims to investigate the effect of low temperature against to bending strength behavior of pipe from composite epoxy with jute fiber reinforcement. The low-temperature treatment was applied through an immersion process in dry ice as long as 60 minutes to produces a temperature of -33oC. The pipe composite was manufactured in lamination three layers of jute fabric using the vacuum injection molding process (VRTM). Then, the strength of the composite pipe was tested on the three-point bending method according to the ASTM D 790 standard. The testing results show that composite pipe with low-temperature treatment has a flexural strength average of about 76.559 MPa. Meanwhile, the compo-site pipe without treatment shows the strength of flexural average of about 52.435 MPa. They have the strength of flexural inclination is an average of 68%. In addition, the failures of composite in three-point bending test shows a shrank mode on the compression side and flat tearing at tension side due to the material becomes brittle. The conclusion that low-temperature treatment has an effective influence on the pipe composite mechanical properties.